Identifying the Driving Factors and Individual Attachment to Terrorist Groups: A Case Study of a Former JAD Member - Ariyanta, Admiral; Priyanto, Sapto; Subandi, Imam (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Terrorist radicalization has become a tangible threat to global security, including in Indonesia, as many individuals remain exposed to radical ideologies and join terrorist groups. This study aims to understand the driving factors behind individuals' decisions to enter and the causes of their attachment to terrorist groups, using the case study of SMA (a former member of JAD). This research employs a qualitative method through direct interviews with SMA. The findings indicate that terrorism radicalization is a gradual process of transformation involving changes in worldview, identity shifts, and strengthened loyalty to the group, culminating in an individual's readiness to carry out acts of terror. In the case of SMA, social injustice and relative deprivation, particularly towards state institutions, served as driving factors for joining a terrorist group. The study also finds that individual attachment to terrorist groups may be influenced by psychological, social, and emotional aspects, wherein the terrorist group can serve as an ideological “home” for its members, and the “Ustad” within the group may function as an ideological “father.” Therefore, deradicalization programs should not only focus on ideology or the fulfillment of economic needs but also consider psychological and social aspects. This is because the driving factors and stages of radicalization for each terrorist group member are unique, thus requiring differentiated handling approaches.